Saminist’s Indigenous Knowledge In Water Conservation in North Karts Kendeng Sukolilo - Mojo, Endrat (Komunitas, 2015)
Saminist is  indigenous peoples and a  local communities at North karts Kendeng. Saminist   expected that North Karts Kendeng maintained and conserved  continuity to be able to contribute to the life around this region  especially abundant water. Water is one of the main needs of living beings on Earth, besides that water is a primary requirement of farmers in farming communities. Saminist as traditional community who only permitted to be farmers  still practice the environmental wisdom from  their heritage which aims to preserve the natural environment so that they could alive depend on nature around, especially Saminist just sack their  business of farming crops that are not market oriented as much farming is done farmers in general. They tried to maintain a relationship of harmony between communities around the North  Karts Kendeng to conserve North Karts Kendeng region from mining destruction, the negative impacts from mining in this region was disappears of water and others impacts  such as natural disaster, flood, rough, and danger of tornado.  North Karts Kendeng Sukolilo have  79 springs and 24 caves spread across 3 sub-district namely  Sukolilo, Kayen and Tambakromo. Abundant natural resources certainly is a gift that needs to be maintained and conserved.  To maintain and conserve this region with planting the three, not mining the rocks, maintain local wisdom, and refusal cement industry in North Karts Kendeng Sukolilo.